Analisis Pengaruh Kepercayaan dan Harga Terhadap Loyalitas Pelanggan Dimediasi Kepuasan Pada PT. Telkomsel di Kota Kediri - Nur Laely (Universitas 17 Agustus 1945 Surabaya, 2016)
To know clearly about customer satisfaction and loyalty at PT. Telkomsel in KediriTown of East Java, this research focused on the models of customer’s satisfaction andloyalty increase based on customer trust, and product prices. From the testing results ofthe model in this research, by using random sampling, structural equation modeling (SEM)analysis, and the assistance of software Amos 20, on 150 respondents, it was able toexplain the relationship between trust, price, and customer satisfaction on the customerloyalty in PT. Telkomsel in Kediri Town of East Java. In this research, it was obtained astrong influence of customer trust and satisfaction, amounting to 0.429, and a stronginfluence between customer satisfaction and loyalty, that is of 0.233, it showed that, withthe rising customer trust, it will increase customer satisfaction, which in turn raise theloyalty of PT. Telkomsel customers.In this study, it also found the negative effects of price and customer satisfaction,amounting to -0.089, and the strong influence of negative between price and loyalty ofcustomers, that is of -0.406, this case indicated that, with the rising of product prices, itwill lower customer satisfaction, which further lowers the loyalty of PT. Telkomselcustomers.Keywords: trust, prices, satisfaction, and customer loyalty